HUBUNGAN KADAR BUN DAN KREATININ PADA PASIEN YANG DIDUGA MENDERITA GAGAL GINJAL KRONIK DI RSUD DR. SOEGIRI LAMONGAN - Riski Dwi Prameswari; Venny Vilayati (Journals of Ners Community, 2019)
Kidney is one organ that plays an important role in the process of excretion and generally serves to regulate water balance, regulate the concentration of salt in the blood, alkaline balance and excretion of waste material. One disease in which the kidneys Chronic Renal Failure. Chronic renal failure is a clinical syndrome caused by a decrease in kidney function is a chronic, progressive and lasted quite advanced. Laboratory tests can be done to help diagnose chronic kidney disease is the one that examination of BUN and creatinine, because both these checks can be an indicator of a strong and specific to kidney function.From the data analysis with statistical test of correlation showed a positive correlation between the levels of BUN and creatinine in patients suspected of suffering from chronic renal failure is evident from the significant value = 0.004. Because of the significant value <α or 0.004 <0.05 then H0 rejected and H1 accepted which means there is no correlation between BUN and creatinine in patients suspected of suffering from chronic renal failure